Islamic Education on Science, Peace, and Development in Thought of Said Nursi - Said, Mohamed Mohamed Tolba (Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2018)
Bediüzzaman Said Nursi desired to fit in the divine and modern knowledge with the resolution to authenticate the facts for assurance. To overcome many obstacles and continued in the teaching of Islam requires education to inspire learning approach across all societies. Development is more effective when it is combined with Character and religious education. Therefore he thrived to release the Islamic world from the dungeons of ignorance and poverty; with vision and progressive action, believed that a greater demand on learning could position a society into a very strong and higher position. He had a great inclusiveness quotient and promoted innovation to be brought into the Islamic Society, by appreciating the good elsewhere. Improved groundwork in science adequately requires extensive work so as to surge up the quality, professionalization, latent skilling and advance learning in people, so that they rise high and value effort to be considerably effective than as it was earlier. Without any Islamic connect learning is assumed to have been only invented, but of no real use.